Federalismo e relaç\~oes intergovernamentais no Brasil: Dinâmicas, impasses e consensos atuais (revelados por gestores públicos estaduais) - Aristides Monteiro Neto; Ricardo Ismael; Eduiges Romanatto; Elmer Nascimento Matos; Tomás Pinheiro Fiori; Walter Marcos Knaesel Birkner (Instituto de Pesquisa Econômica Aplicada (IPEA), 2017)
– This study presents results obtained from interviews took by a team of researchers from a chosen group of public servants in four Brazilian state governments (Sergipe, Goiás, Rio Grande do Sul and Santa Catarina) during the year of 2013. Our aim was to question such policy makers about intergovernmental relations developed by them in their everyday public duties. It was investigated their own positions on institutional issues, successful and critical points, as well as their views on agreements and negotiations among federative entities. In sum, our interests lied on elements to realize and contrast dynamics, obstacles and consensus present on intergovernmental relations in Brazilian federalism.
Keywords: H77; 330; federalism; intergovernmental relations; state capacities